Pengaruh Trust in Leader dan Komunikasi Terhadap Kinerja Karyawan Melalui Motivasi Pada PT. Agrindo Sawit Mandiri Surabaya - Ichwan Bagus Airlangga; Joko Mandiri (Yos Soedarso Economic Journal (YEJ), 2022)
Human resources are the main component in an organization, which are planners and active actors in every organizational activity. To achieve an organizational goal must meet good work results in order to increase employee performance. Basically, to achieve employee performance in an organization, there are several factors that must be considered, namely trust in leaders, communication and motivation. PT. Agrindo Sawit Mandiri Surabaya is a company engaged in the processing of crude palm oil which produces oil and also has many employees with various levels of education, so a leader must be able to control and control his employees and provide direction and motivation so that employees are able to work. optimally even though employees have different levels of education. The purpose of this study was to analyze the influence of trust in leader and communication on employee performance through motivation as an intervening. The population of this study were all HR employees who worked at PT. Agrindo Sawit Mandiri, amounting to 775 respondents. The sampling method using the Slovin formula obtained a sample size of 263 respondents. Data analysis was performed through PLS-SEM using the SmartPLS program. The results showed that directly trust in leader, communication and motivation had a positive and significant effect on employee performance then indirectly trust in leader and communication had a significant effect on employee performance through motivation.